Effects of Vertically Propagating Mountain Waves During a Strong Wind Event Over the Ross Ice Shelf, Antarctica - Chenoli, Sheeba Nettukandy; Turner, John; Samah, Azizan Abu (Indian Academy of Sciences, 2018)
Weather forecasting in the Antarctic presents many challenges, with strong wind events (SWEs) often disrupting air and field operations. Here, we study the mechanisms responsible for a SWE (maximum wind speed 22 ms -1 ) that occurred at the McMurdo/Scott Base region on the Ross Ice Shelf (Antarctica) over 12-13 October 2003. The study is based on in situ observations, satellite imagery and output from the Antarctic mesoscale prediction system (AMPS) model. The event occurred during the passage of a complex low pressure system that increased the pressure gradient between the northwest Ross Ice Shelf and the continental high, initiating a strong southerly flow. AMPS simulations as well as upper air sounding profiles from McMurdo station showed the involvement of large amplitude vertically propagating mountain waves over the area. The amplification of mountain waves by the self-induced critical level reflected all the energy back towards the surface to generate high downslope winds.